Paper 20: The Relationship of Schottle's Point to the Medial Distal Femoral Physis: A Digitally Reconstructed Radiograph and 3-Dimensional Computed Tomography Study. Issue 7 (30th July 2022) - Metz, Allan; Froerer, Devin; Mortensen, Alexander; Aoki, Stephen; Featherall, Joseph
Objectives: There is significant controversy regarding ideal medial patellofemoral ligament reconstruction (MPFLR) femoral tunnel position in the pediatric setting. The authors identified 3 main gaps in knowledge. First, the position of the radiographic MPFLR start point (Schottle's point) relative to the medial distal femoral epiphysis is not well defined. Second, although anatomic studies have suggested tunnel trajectories that avoid physeal contact, these trajectories are not based upon the widely used Schottle's point, providing limited intraoperative utility. Third, prior studies provide conflicting data regarding position of the MPFL origin relative to the distal femoral physis, particularly in younger patients. The purpose of this study was to determine the proximity of Schottle's point to the medial distal femoral physis and the medial epicondyle using a digitally reconstructed radiographs (DRR) and three-dimensional computed tomography (CT) models. Methods: The institutional picture archiving and communication system (PACS) was queried for CT imaging studies of pediatric knees with open physes. CT data were imported to a Python based, open-source image processing software and were transformed to create true lateral digitally reconstructed radiographs (DRR) (Figure 1) and 3-dimensional (3D) renderings of the distal femur (Figure 2). Schottle's point and the medial epicondyle were registered using fiducial markers and 3D distance measurements were then obtained from Schottle's point on the medial cortex to 1) the medial epicondyle, 2) the physeal point directly superior to Schottle's point, and 3) the shortest distance to the medial physis on the cortical surface. A 6-millimeter circle was used to simulate reaming diameter and physeal intersections were tabulated. Results: 49 pediatric knee CT scans with open physes were included in the data. Average patient age was 13.0 ± 2.3 years (range: 6-17 years). Mean minimum distance from the medial physis to Schottle's point was 9.9 mm ± 3.0mm (range: 3.4-16.1 mm) (Figure 3). In 49 of 49 cases (100%), Schottle's point was distal to the physis. Schottle's point was localized at a mean distance of 7.5mm ± 3.14mm posterior to the medial epicondyle and 6.1mm ± 2.9mm superior to the medial epicondyle. Using a 6mm reaming diameter, 3 (6%) femurs in our study would have violation of the medial distal femoral physis. Moving the start point 3mm distally would result in 0 of 49 (0%) having physeal injury. Conclusions: Historically, characterizing the position of the origin of the MPFL on the medial condyle relative to the medial distal femoral physis has been challenging. Prior cadaveric studies have suggested the MPFL originates proximal to the physis in younger patients (<7 years). However, more recent cadaveric studies have challenged this idea, finding the bony landmarks of the MPFL origin to be distal to the physis. Although these studies have sparked significant discussion regarding the pediatric MPFL origin, they have small numbers of specimens. Using a more surgically relevant approach, the present study demonstrates that Schottle's point is consistently distal to the distal femoral physis. Prior studies have suggested anterior and distal drill trajectories that may minimize physeal injury. Although useful, these studies do not assess drilling path relative to the commonly used radiographically identified starting point, Schottle's point. The present study complements this prior work by addressing the radiographic start point upon which the drill trajectory is based intraoperatively. Based on the present study, the use of Schottle's point without distalization would lead to physeal injury in 6% of cases. Further, prior cadaveric anatomic studies are subject to limitations of the availability and expense of pediatric specimens and are therefore limited to small sample sizes. The methodology of the present study, by using readily available fine cut CT data, is not subject to such constraints. The present investigation offers a larger sample size than any previously published pediatric MPFL anatomic study and uses a highly accurate and repeatable methodology. This unique methodology may be more broadly applicable to the study of pediatric procedures near the physis. The radiographically defined surgical start point for MPFL femoral tunnel placement (Schottle's point), is consistently distal to the medial distal femoral physis. Mean minimum distance from Schottle's point to the physis on the medial cortex is 9.9mm. Using Schottle's point for the start of tunnel drilling leads to physis violation in 6% of cases, when using a 6mm reamer. Distalization of the start point by 3mm leads to avoidance of physeal injury in all cases. Figure 1. Digitally Reconstructed Radiograph with Identification of Schottle's Point Figure 2. 3D Rendering with Physeal Distance Measurement Figure 3. Saggital Plane Plot of Schottle's Point and Closest Point on Medial Physis